Selenolation of Aryl Iodides and Bromides Enabled by a Bench‐Stable PdI Dimer. Issue 40 (17th April 2019) - Senol, Erdem; Scattolin, Thomas; Schoenebeck, Franziska
Abstract: The use of an air‐ and moisture‐stable dinuclear Pd I complex as an efficient catalyst for the formation of C(sp 2 )−SeR bonds is here reported. The privileged reactivity of the Pd I dimer allows for the direct use of selenolates as nucleophiles in the cross‐coupling. Although previous methodologies suffer from catalyst poisoning through the formation of Pd‐ate complexes, the mechanistically distinct dinuclear Pd I catalyst circumvents this challenge. A wide variety of aryl bromides and iodides were efficiently coupled under relatively mild reaction conditions with broad functional group tolerance. Mechanistic and computational data are presented in support of direct Pd I reactivity. Abstract : Pd I dimer in action ! The use of an air‐ and moisture‐stable dinuclear Pd I complex as an efficient catalyst for the formation of C(sp2)−SeR bonds is here reported. The privileged reactivity of the Pd I dimer allows for the direct use of selenolates as nucleophiles in the cross‐coupling. A wide variety of aryl bromides and iodides were efficiently coupled under relatively mild reaction conditions with broad functional group tolerance. Mechanistic and computational data are presented in support of direct Pd I reactivity.